Armour : materials, theory, and design - Hazell, Paul J. (CRC Press, 2022)
Updated throughout for the new edition, Armour: Materials, Theory, and Design covers extant and emergent protection technologies driving advances in armour systems. Covering materials, theory and design, the book has applications in vehicle, ship, personnel and building use. Introducing a wide range of armour technologies, the book is a key guide to the technology used to protect against both blasts and ballistic attacks. Chapters cover bullets, blasts, jets and fragments, as well as penetration mechanics. The new edition builds on the previous one, discussing ceramics and metallic materials as well as woven fabrics and composite laminates. Detailing modern technology advancements, the second edition has also been expanded to include improved explanations on shock mechanisms and includes significantly more figures and diagrams. An essential guide to armour technology, this book outlines key ways to implement protective strategies applicable for many types of conflict.
Keywords: Armor.; Armor -- Design and construction.; Armor -- Materials.; elektronické knihy; electronic books